COMPARISON OF THE EFFECTIVENESS OF COOPERATIVE MODEL OF STAD TYPE AND PROBLEM-BASED LEARNING MODEL WITH SCIENTIFIC APPROACH ON SEQUENCE AND SERIES LESSON MATERIAL IN CLASS X IPA AT SMAN 1 DUAMPANUA - H Rais (Universitas Negeri Makassar, 2015)
The study aims at examining (1) the difference of learning outcomes in class which used problem-based learning model and cooperative learning model of STAD type, (2) the difference of learning outcomes in class which used problem-based learning model and cooperative learning model of STAD type, (3) the comparison of effectiveness of problem-based learning model and cooperative learning model of STAD type with scientific approach. The study is an experimental research with pretest and posstest control group design using the treatment twice and using the instrument: tests of learning outcomes, student activity sheets observation and questionnaire responses of students. The population of the study was students of class X IPA at SMAN 1 Dupamanua in Pinrang district. The samples were two classes, namely class X IPA 2 as the experiment class I using problem-based learning model and class X IPA 3 as the experiment class II using cooperative learning model of STAD type. Samples were selected by employing random sampling technique. Data of the test of learning outcomes were analyzed by employing on-sample test analysis and independent sample test, and questionnaire was analyzed using descriptive analysis. The results of the study revealed the (1) there was significant improvement between the class which used problem-based learning model and cooperative of STAD type indicated by the significant P < 0.05, (2) the learning outcomes used problem-based learning model was higher which was 78 than cooperative learning model of STAD type which was 74. (3) the students gave positive response on the use of problem-based learning model with 17 which gave excellent response and 83% gave good response and 62% gave good response. The problem-based learning model showed higher result on sequence and series lesson material than cooperative learning model of STAD type